THE ROLE OF TRANSLATION SKILL IN DEVELOPING STUDENTS’ POTENCY: A CASE STUDY IN ENGLISH DEPARTENT, MUHAMMADIYAH UNIVERSITY OF SURAKARTA - Anam Sutopo (Universitas Muhammadiyah Surakarta, 2009)
The study of translation concerns with meaning and transferring the messagefrom source language to target language. Translation is also regarded as a science,a skill and an art. This study aims at identifying the role of translation skill fordeveloping the English department students’ potency. This study applies a qualitative research. It takes location in Muhammadiyah University of Surakarta. Thesources of data are informant, event and document. The collected data are takenfrom an open-questionnaire, in depth interviewing, observation and content analysis. To analyze the collected data, the writer uses an interactive analysis. The resultof the research shows that there are five roles of translation skill for developingEnglish department students’ potency. They are academic, practical, commercial,psychological, and social roles.Keywords: translation, skill, and english department students